(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The Museum of Image and Sound of Alagoas is one of the state’s cultural assets. Therefore, this study aims to examine the management and dissemination of photographic and sound collections, propose changes to ensure digital preservation in compliance with national and international standards and recommendations, and provide authentic and complete access. It is a qualitative case study of a descriptive-exploratory nature, carried out through occasional visits and unstructured interviews with staff. Therefore, it highlights the need to create management policies and a reliable digital environment to preserve its collection.